Brigatinib as a treatment of ALK-positive non-small cell lung cancer. Issue 5 (3rd September 2021) - De Carlo, Elisa; Stanzione, Brigida; Del Conte, Alessandro; Revelant, Alberto; Bearz, Alessandra
ABSTRACT: Introduction: Anaplastic lymphoma kinase (ALK) gene rearrangements and resulting fusion proteins occur in 3%-7% of patients with non-small-cell lung cancer (NSCLC), conferring sensitivity to treatment with ALK Tyrosine-Kinase Inhibitors. After the first-generation ALK inhibitor crizotinib, newer generation ALK inhibitors have been developed and showed greater potency and brain penetration in both crizotinib-naïve and crizotinib-refractory advanced NSCLC patients. Areas covered: Brigatinib is a potent and highly selective second generation ALK inhibitor. Brigatinib is approved by Food and Drug Administration and European Medicines Agency for ALK-positive advanced NSCLC patients previously treated with crizotinib and more recently as first-line treatment in naïve patients. In the current review we present an up-to-date overview of the current and evolving clinical data regarding the biology of the disease, the emerging clinical decision-making and the targeted therapy options in advanced NSCLC harboring ALK translocation, especially focusing on the activity of brigatinib. Expert opinion: Brigatinib shows a deep systemic and intracranial efficacy in both naïve and refractory metastatic ALK-positive NSCLC patients in the clinical studies, which marked its clinical development. Given its efficacy and tolerability brigatinib could be an excellent therapeutic option for the treatment of advanced ALK-positive NSCLC patients.